Diagnostic and prognostic value of polygene methylation detection in ascites - Ma, Yang; Wang, Xueqing; Du, Yun (Frontiers in Genetics, 2025)
ObjectiveTo explore a novel combination of methylation markers for the differential diagnosis of malignant ascites (MA).Materials and methodsA cohort of 164 cancer patients and 20 patients with benign disease presenting with ascites was enrolled. Ascites was tested by means of cytopathological routine diagnosis and DNA methylation detection of SHOX2, RASSF1A, SEPTIN9 and HOXA9 in the cytological specimens. DNA methylation in bisulfite-converted DNA was determined using semi-quantitative methylation-specific real-time PCR (MS-PCR). In addition, Kaplan-Meier method was used to plot the Overall survival (OS) curve based on the methylation status of four genes to explore the relationship between gene methylation status and prognosis of patients with ascites. The Cox regression model was used to analyze the survival factors.ResultsMethy-All-In-One Kit (OncoMe), a novel combination of SHOX2, RASSF1A, SEPTIN9 and HOXA9 methylation, led to an additional 29.9% increase in the detection rate of MA combined with the cytopathological test, resulting in a sensitivity of 76.2%. OncoMe showed high positive detection rates in Breast Cancer (87.5%), Pancreatic Cancer (83.3%), Gastric Cancer (79.5%), Cholangiocarcinoma (72.7%) and Ovarian Cancer (68.3%). Patients in the SHOX2 and SEPTIN9 methylation-positive groups had a significantly higher risk of disease progression than those in the negative groups. The OS of SHOX2 and SEPTIN9 gene methylation test negative group was higher than that of positive group.ConclusionOncoMe has potential for use as a biomarker for the detection of MA. Cytological examination combined with methylation detection can greatly improve the diagnosis rate of malignant ascites. The methylation status of SHOX2 and SEPTIN9 genes is significantly correlated with the prognosis of patients with ascites.